A Comparison of the Effectiveness of Schema Therapy and Mindfulness-Based Cognitive Therapy on Self-Esteem and Psychological Well-Being of Incarcerated Women - Nosrati, Narjes; Rahmanian, Mahdieh; Alibakhshi, Seyyedeh Zahra; Moghanloo, Mahnaz (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to compare the effectiveness of schema therapy and mindfulness-based cognitive therapy on self-esteem and psychological well-being among incarcerated women. Methods and Materials: This quasi-experimental study employed a pretest-posttest-follow-up design with a control group. Forty-five incarcerated women from Rasht Prison in 2024 were selected through convenience and voluntary sampling based on inclusion criteria, including age (35–55), at least one year of incarceration, and absence of clinical psychiatric disorders. Participants were randomly assigned to three equal groups: schema therapy, mindfulness-based cognitive therapy (MBCT), and control. The intervention groups received 8 weekly 90-minute sessions. The Ryff Psychological Well-Being Scale and Crocker Self-Esteem Questionnaire were used to assess outcomes at pretest, posttest, and two-month follow-up. Data were analyzed using repeated measures ANOVA, multivariate analysis of covariance (MANCOVA), and Bonferroni post hoc tests in SPSS-27. Findings: Both schema therapy and MBCT groups showed significant improvements in self-esteem and psychological well-being compared to the control group (p < .001). MANCOVA results indicated significant differences among the three groups in posttest scores of self-esteem and psychological well-being (Wilks’ Lambda = 0.43, F = 9.8, p < .001, η² = 0.79). ANCOVA revealed a significant difference in self-esteem (F = 2.45, p = .038, η² = 0.112) and psychological well-being (F = 24.04, p = .001, η² = 0.649) among the groups. Bonferroni tests showed MBCT had a greater effect on self-esteem, while schema therapy showed superior effects on psychological well-being. Conclusion: Schema therapy is more effective in promoting long-term psychological well-being, whereas MBCT more significantly enhances self-esteem.